2019
DOI: 10.1515/nanoph-2019-0361
|View full text |Cite
|
Sign up to set email alerts
|

Optical binding of nanoparticles

Abstract: Optical binding is a laser-induced inter-particle force that exists between two or more particles subjected to off-resonant light. It is one of the key tools in optical manipulation of particles. Distinct from the single-particle forces which operate in optical trapping and tweezing, it enables the light-induced self-assembly of non-contact multi-particle arrays and structures. Whilst optical binding at the microscale between microparticles is well-established, it is only within the last few years that the exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
46
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(47 citation statements)
references
References 142 publications
1
46
0
Order By: Relevance
“…A review on the latest research on such binding forces at the nanoscale is to be found in Ref. [122].…”
Section: B Optical Bindingmentioning
confidence: 99%
“…A review on the latest research on such binding forces at the nanoscale is to be found in Ref. [122].…”
Section: B Optical Bindingmentioning
confidence: 99%
“…This is particularly clear when the constituents are NPs that are smaller than the wavelength of light 15 , 16 . This interaction, known as optical binding 14 , 17 , 18 , allows formation of regular OM configurations (e.g. 2D arrays with trigonal symmetry or anisotropic arrays with rectangular lattice configurations) with minimal optical information, generally only the overall shape, polarization, phase, and power of the optical beam 17 and the resulting particle configurations are readily visualized by optical microscopy 15 , 19 21 .…”
Section: Introductionmentioning
confidence: 99%
“…It is known that long range interactions manifest structural and dynamic correlations in driven dense colloidal solutions due to hydrodynamic interactions 28 , and in quantum-dot perturbed molten salt solutions 29 . OM configurations self-organize in optical traps in solution and achieve new collective properties due to their electrodynamic interactions and long range (periodic) potentials 14 , 15 , 17 , 18 . The long range interactions create a new richness for understanding isomerizations of OM configurations as they affect the energetics globally and imbue OM systems with many-body interactions and physics.…”
Section: Introductionmentioning
confidence: 99%
“…More generally, while a pair of scatterers tends to self-organize at a distance equal to an integer number of optical wavelengths, larger systems suffer from diffraction effects which alter this spacing, but also the system stability [15]. Finally, despite the fact that the binding force scales poorly with decreasing scatterer size [16], OB has recently attracted a lot of attention for nanoparticles, as it appears as a potential mechanism for self-structuring at the nanoscale [17].…”
Section: Introductionmentioning
confidence: 99%